Neural Dysconnectivity in the Hippocampus Correlates With White Matter Lesions and Cognitive Measures in Patients With Coronary Artery Disease - Niu, Jianhua; Zhang, Jingchen; Yan, Jueyue; Xu, Zhipeng; Fang, Xing; You, Jingyu; Liu, Zhihai; Wu, Weifang; Li, Tong (Frontiers in Aging Neuroscience, 2022)
Purpose: Degree centrality (DC), a graph-based assessment of network organization was performed to explore the neural connectivity changes in coronary artery disease (CAD) patients compared with healthy controls and their correlation with cognitive measures. Methods: thirty CAD patients and 36 healthy controls were included in our study. All participants underwent functional magnetic resonance imaging (fMRI) of the brain. We performed DC analysis to identify voxels that showed changes in whole-brain functional connectivity with other voxels. DC was measured by the fMRI graph method and comparisons between the two groups were done. All participants underwent neuropsychological assessment (Montreal Cognitive Assessment, MoCA and Mini-Mental State Examination, MMSE). Results: CAD patients showed significantly decreased DC value (P < 0.005) in the right hippocampus (hippocampus_R), right lingual gyrus (lingual_R), and significantly increased DC value (P < 0.005) in the left middle frontal gyrus (Frontal_Mid_L) when compared with healthy controls respectively. DC value in the hippocampus_R significantly correlated (P < 0.00) with MMSE and MoCA scores in CAD patients. Fazekas scores in CAD patients showed a significant correlation (P < 0.001) with DC value in the hippocampus_R. Conclusions: These findings suggest that reduced cerebral neural connectivity in CAD may contribute to their cognitive impairment and white matter microstructural damage.